Analisis Perbandingan Degree of Financial Leverage Antara PT. Indocement Tunggal Prakarsa, Tbk dan PT. Holcim Indonesia Tbk - Mulyati, Isti; Rimawan , M. (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
This study was conducted with the aim of determining the significant difference in the Degree of Financial Leverage between PT Indocement Tunggal Prakarsa, Tbk and PT Holcim Indonesia, Tbk for the period 2012-2023. The type of research used by researchers in this study is a comparative research type. The research instrument used is a list of tables containing net profit, EBIT, and EPS data obtained from the balance sheet and profit and loss financial statements at PT. Indocement Tunggal Prakarsa, Tbk and PT. Holcim Indonesia, Tbk from 2012-2023. The population used in this study is all financial statements of PT. Indocement Tunggal Prakarsa, Tbk since it was listed on the IDX from 1989 to 2023, which is for 34 years and PT. Holcim Indonesia, Tbk from 1977 to 2023, which is for 46 years. The sample in this study is the financial statements of PT. Indocement Tunggal Prakarsa, Tbk and PT. Holcim Indonesia, Tbk for 12 years, namely from 2012 to 2023. The sampling technique used in this study is purposive sampling. The data collection techniques used in this study are documentation and literature studies. The documentation referred to in this study is the financial statements of PT. Indocement Tunggal Prakarsa, Tbk and PT. Holcim Indonesia, Tbk in the form of profit and loss statements from 2012 to 2023. The literature study referred to in this study is to search for and collect information through books and journals. The data analysis technique used in this study is the Degree of Financial Leverage (DFL) analysis. The results of the study can be concluded in this study are that there is no significant difference in the Degree of Financial Leverage at PT Indocement Tunggal Prakarsa, Tbk, and PT Holcim Indonesia, Tbk